The Music Creative Research: ‘The Phenomenon’ for Saxophone and Wind Symphony Part II - ศุภจิตรา, ประหยัด (Parichart Journal, 2017)
The Creative Music Research: ‘The Phenomenon’ for Saxophone and Wind Symphony is the music composition inspired by the Thai spectacularly traditional masterpiece namely “Bulun Loy Luen” the music which was composed by “Phra Phutthaloetla Naphalai” (1767-1824, King Rama II of Chakri Dynasty). His majesty had taken a forgotten melodic fragment called “Bulun Loy Luen” whereby it was delicately developed and well-crafted designed to be the newly written master piece. The Phenomenon is also the composition that preserved the original theme by presenting as the retrograde fragment of the middle section (Moderato), The first section has been presented as the augmentation of the main theme (Allegro), and the finale section is the diminution of the them (Allegretto). Those three unique sections have been connected by the transition which was presented as the third section (Scherzo). The form of rhapsodic suite has been applied in order to utilize the character piece into a highly imaginative idea of form, moreover making it suits to the color between Saxophone and Wind Symphony. The entire duration of the piece is approximately 45 minutes. The composer has been inspired by the musical performing techniques and the variety of improvising rhythmic patterns, which has naturally been used in southern Thai folk music as a composing material. This rhapsodic suite is derived from imaginative ideas of composing. Meanwhile, the integration by combining between creative ideas and composing techniques of contemporary music has played a vital role in the entire compositio